RFLP clusters of rifampicin resistant and susceptible Mycobacterium tuberculosis strains in Western province of Sri Lanka: Clusters of M. tuberculosis strains in Sri Lanka - Adikaram, Chamila Priyangani; Wijesundera, Sandya Sulochana; Perera, Jennifer (The Journal of Infection in Developing Countries, 2017)
Introduction: Continuous studies on genetic diversity of Mycobacterium tuberculosis could enhance the awareness on transmission, control and prevention of tuberculosis (TB). In this study, we investigated current genetic diversity of TB and rifampicin resistant TB by, Restriction Fragment Length Polymorphism (RFLP) based on fingerprinting of the IS6110 insertion sequence, in the Western province of Sri Lanka, the famous touristic destination with the highest TB burden in the country. Methodology: Genomic DNA extracted from susceptible and rifampicin resistant TB strains (confirmed for rpoB gene point mutations) were digested with PvuII restriction enzyme, electrophoresed and subjected to Southern transfer. The blots were hybridised with IS6110 probe and visualized using a chemiluminescence detection. Results: The number of copies of IS6110 per isolate varied from 1 to 14. The dendrogram revealed a total of 68 distinct strains among 77 TB isolates and they belonged to nine clusters. Both rifampicin resistant and susceptible strains were distributed in all clusters. This evaluation revealed the absence of genetically identical or strong relatedness between susceptible and resistant isolates. However, clonal expansion was detected in transmission of both TB and rifampicin resistant TB. In addition, the resistant isolates having the novel mutation had no clonal relatedness. Conclusion: This is the first observational study regarding clonal expansion of TB in Sri Lanka. Thus, further investigation on genotypes, clonal expansion and transmission of drug resistance using additional markers would be useful for controlling TB.